Endometrial response to conceptus-derived estrogen and interleukin-1β at the time of implantation in pigs - Ka, Hakhyun (J Anim Sci Biotechnol, 2018)
The establishment of pregnancy is a complex process that requires a well-coordinated interaction between the implanting conceptus and the maternal uterus. In pigs, the conceptus undergoes dramatic morphological and functional changes at the time of implantation and introduces various factors, including estrogens and cytokines, interleukin-1β2 (IL1B2), interferon-γ (IFNG), and IFN-δ (IFND), into the uterine lumen. In response to ovarian steroid hormones and conceptus-derived factors, the uterine endometrium becomes receptive to the implanting conceptus by changing its expression of cell adhesion molecules, secretory activity, and immune response. Conceptus-derived estrogens act as a signal for maternal recognition of pregnancy by changing the direction of prostaglandin (PG) F(2α) from the uterine vasculature to the uterine lumen. Estrogens also induce the expression of many endometrial genes, including genes related to growth factors, the synthesis and transport of PGs, and immunity. IL1B2, a pro-inflammatory cytokine, is produced by the elongating conceptus. The direct effect of IL1B2 on endometrial function is not fully understood. IL1B activates the expression of endometrial genes, including the genes involved in IL1B signaling and PG synthesis and transport. In addition, estrogen or IL1B stimulates endometrial expression of IFN signaling molecules, suggesting that estrogen and IL1B act cooperatively in priming the endometrial function of conceptus-produced IFNG and IFND that, in turn, modulate endometrial immune response during early pregnancy. This review addresses information about maternal-conceptus interactions with respect to endometrial gene expression in response to conceptus-derived factors, focusing on the roles of estrogen and IL1B during early pregnancy in pigs.